Patient-reported outcomes in adoptive cell-therapy trials: mind the gap - Manuela Eicher; Massimo Di Maio; George Coukos; Lionel Trueb; Matteo Morotti; Eleonora Ghisoni; Sara Colomer-Lahiguera (Journal for ImmunoTherapy of Cancer)
Adoptive cell therapies (ACT) have demonstrated promise in the treatment of patients with cancer, leading to long-lasting responses and, in some cases, even cure. Technological advances have brought these individualized therapies closer to reality, establishing them as credible therapeutic option. However, to date, few efforts have been made to understand patients' experience during ACT trials. Patient-reported outcomes (PROs) and patient-reported outcome measures (PROMs), which are instruments used to report PROs, are increasingly being used in oncology to capture patients’ perspective, provide real-world data on treatment safety, and support decision-making processes, such as health economic decisions. Due to the inherent complexity of ACT, the inclusion of PROMs in this field remains limited. In this commentary, we discuss the benefit of capturing PROs in ACT trials, the challenges of PROM administration and collection, and we propose simple and actionable recommendations to promote their adoption in ACT trials.